PERAN PEMERINTAH DALAM PEMBERDAYAAN USAHA BATIK TULIS DI KABUPATEN KEBUMEN - Arifah, Nur; Taufiq, Achmad; Astuti, Puji (Journal of Politic and Government Studies, 2015)
AbstractionEmpowerment of community based of is growing in the age of globalization. One effort to empower entrepreneurs based in Kebumen is reviving the batik industry. This is because the potential of batik in Kebumen were still occupied by many people, so it is expected to be the mode of batik industry is more modern. Therefore, the Government Kebumen has committed to the empowering of the typical batik artisans Kebumen. This is the reason the research conducted, with the aim of seeing the extent to which the success the empowerment of batik.This study used a qualitative descriptive research type with data collection through interviews, collect data in the field with the speaker directly and documentation, namely data collection through the archives, books, and other sources. mechanical analysis performed by reduction data and interpreting the results of interviews with various sources.From the research found that there are several successful programs, among others, the establishment of clusters of excellence, support equipment, exhibits, capital, the provision of the copyright and trademark. But there are also programs that have not been as successful as training and marketing which explains that the program is still no commitment of the Government of Kebumen.Recommendation of the research findings is the need to build a sustainable commitment of build cooperation among sectors in the scope of the Government Kebumen, so that training and marketing programs in the empowerment of batik in Kebumen can succeed.